2021
DOI: 10.3390/f12010069
|View full text |Cite|
|
Sign up to set email alerts
|

Reciprocal Common Garden Altitudinal Transplants Reveal Potential Negative Impacts of Climate Change on Abies religiosa Populations in the Monarch Butterfly Biosphere Reserve Overwintering Sites

Abstract: Research Highlights: Reciprocal altitudinal transplants of Abies religiosa seedlings within the Monarch Butterfly Biosphere Reserve (MBBR) allow prediction of the impacts of climatic change, because they grow in sites with a climate that differs from that of their origin. Background and Objectives: Climatic change is generating a mismatch between the sites currently occupied by forest populations and the climate to which they have adapted. This study determined the effect on the survival and growth of A. relig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…Together with the growth-based results, these findings suggest that the warmer and drier conditions expected across much of northern Canada under climate change [3] may reduce survival, but that surviving trees may grow at a faster rate until a certain magnitude of climate warming is reached. Cruzado-Vargas et al [41] reported similar findings along an altitudinal gradient in Mexico. Disparity between growth and survival outcomes has been reported previously [42,43], suggesting that multiple performance metrics may be needed to fully understand climate change responses of northern tree populations.…”
Section: Discussionmentioning
confidence: 61%
“…Together with the growth-based results, these findings suggest that the warmer and drier conditions expected across much of northern Canada under climate change [3] may reduce survival, but that surviving trees may grow at a faster rate until a certain magnitude of climate warming is reached. Cruzado-Vargas et al [41] reported similar findings along an altitudinal gradient in Mexico. Disparity between growth and survival outcomes has been reported previously [42,43], suggesting that multiple performance metrics may be needed to fully understand climate change responses of northern tree populations.…”
Section: Discussionmentioning
confidence: 61%
“…Spatially variable selection has been reported in other Neotropical species, the results for S. thurberi point in a similar direction [77]. Still, evidence of local adaptation needs to be assessed and the intensity and direction of selection quantified, requiring comparison with phenotypic traits and assessment of survival over time [78]. We did not find higher levels of genetic diversity in what were the likely Pleistocene refuges as found by Sanderson et al [79] for saguaro with many more markers.…”
Section: Discussionmentioning
confidence: 91%
“…conditions. In this type of studies, it is expected that the provenance best coupled to the climate of the trial site will have the best performance and the others will show differences, in part, related to the magnitude of the weather differences between the site of origin and the trial site (Cruzado-Vargas et al, 2021;Sáenz-Romero et al, 2017). A variant of the above are the common garden trials where optimal conditions are provided (as far as possible) to the set of provenances to favor the expression of their growth potential, and with this, quantify whether or not there is genetic differentiation between them.…”
Section: Introductionmentioning
confidence: 99%
“…de diversos orígenes geográficos (procedencias) bajo las mismas condiciones ambientales. En este tipo de estudios se espera que la procedencia mejor acoplada al clima del sitio de ensayo tenga el mejor desempeño y las demás muestren diferencias, en parte, relacionadas con la magnitud de la diferencia climática entre el sitio de origen y el de ensayo (Cruzado-Vargas et al, 2021;Sáenz-Romero et al, 2017). Una variante de lo anterior son los ensayos de jardín común donde se proveen condiciones óptimas (en la medida de lo posible) al conjunto de procedencias con la finalidad de favorecer la expresión de su potencial de crecimiento, y con ello, cuantificar si existe o no diferenciación genética entre ellas.…”
Section: Introductionunclassified